What matters when it comes to measuring Age‐Friendly Health System transformation. Issue 10 (22nd August 2022) - Burke, Robert E.; Ashcraft, Laura Ellen; Manges, Kirstin; Kinosian, Bruce; Lamberton, Cait M.; Bowen, Mary E.; Brown, Rebecca T.; Mavandadi, Shahrzad; Hall, Daniel E.; Werner, Rachel M.
Abstract: Thousands of health systems are now recognized as "Age‐Friendly Health Systems, " making this model one of the most widely disseminated – and most promising‐ models to redesign care delivery for older adults. Sustaining these gains will require demonstrating the impact on care delivery and outcomes of older adults. We propose a new measurement model to more tightly link Age‐Friendly Health System transformation to outcomes within each "M" (What Matters, Medications, Mobility, and Mentation). We evaluated measures based on the following characteristics: (1) conceptual responsiveness to changes brought about by practicing "4Ms" care; (2) degree to which they represent outcomes that matter to older adults; and (3) how they can be feasibly, reliably, and validly measured. We offer specific examples of how novel measures are currently being used where available. Finally, we present measures that could capture system‐level effects across "M"s. We tie these suggestions together into a conceptual measurement model for AFHS transformation, with the intent to spur discussion, debate, and iterative improvement in measures over time.